Intramuscular Hibernoma: A Rare Tumour in Buttock - Naik, Reena (J Clin Diagn Res, 2015)
Hibernomas are benign tumours of brown fat that does not recur after complete excision. These tumours are found most often in adults and most commonly in thigh. Four morphologic variants of hibernoma are identified: typical, myxoid, spindle cell, and lipoma-like. The most common histologic type is typical variant. In this report, we present the clinical, morphological features and discuss the differential diagnosis of a typical variant of intramuscular hibernoma.